THE DISRUPTION OF HUMANITARIAN INNOVATIONS IN THE SPACE OF GLOBAL INFORMATION NETWORKS - Ягодзінський, С. М. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The article investigates the contents of humanitarian innovations in postmodern culture. Relying on the fact that the innovative activities in the information age is a social need, the author puts a question about the nature of human innovations. In the space of global information networks humanitarian innovations turn to their socio-cultural media capacity and the main source of social information broadcast